THE NECESSITY AND IMPORTANCE OF DEVELOPING SOCIAL AND INFORMATION COMPETENCE IN STUDENTS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2025)
The most important characteristic of the modern world is the globalisation of information. In modern conditions, the large-scale information platform created with the help of digital technologies reflects a certain, one could say, the main part of the activity of each social subject. Interpersonal communications, based on the technical and functional capabilities of information technologies, at first glance seem very simple and safe. However, this process, which is the most effective in the manipulation of personality and requires relatively small economic costs, is extremely dangerous in nature. To prevent this risk, it is important to develop social and information competence in young people, especially students. This is the focus of this article.